New Advances in Soil Pollution and Remediation (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint reports on new advances in basic and applied research of soil pollution and remediation. A list of contaminants are targeted, including toxic metal(loid)s (e.g., Pb, As, Sb, and multi-metals), organic contaminants (e.g., organochlorine pesticides, phenanthrene, and petroleum), and antibiotics (e.g., sulfadiazine). The occurrence, environmental behaviors, and risks of these contaminants are explored. Special attention is devoted to techniques for the remediation of polluted soils, such as stabilization/solidification, photocatalytic degradation, and thermal desorption. This reprint provides new insights into soil pollution and remediation.